(untitled) (Revista Estudios Psicológicos, 2022)
Background: intimate partner violence is a social and public health problem that mainly affects the female population around the world, considering it a form of exclusion and violation of rights that can be addressed in a multicausal and multidimensional framework. Objective: to relate socioeconomic factors (employment status, level of education and social stratum) and sociodemographic factors (age and marital status) with the types of violence that occur in intimate partner relationships among women in the city of Bucaramanga, Colombia. Method: a quantitative, descriptive and correlational approach was followed, 333 women aged between 20 and 50 years were taken as a sample. Two instruments called: sociodemographic and socioeconomic data and Partner Violence against Women (VPM) were applied. Results: it was determined that there is a relationship between sociodemographic and socioeconomic factors with the types of physical, sexual and psychological violence.